1999
DOI: 10.1177/002199839903301904
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Negative Poisson's Ratio in Randomly Oriented Quasi-Isotropic Composite Laminates

Abstract: In isotropic materials, it is known that values of Poisson's ratio larger than one half are thermodynamically inadmissible, for such values would lead to negative strain energy under certain loads. Although a negative Poisson's ratio is not forbidden by thermodynamics, it is rare in crystalline solids. With the development of modem fiber reinforced composite materials, the effective Poisson's ratio of laminated fiber reinforced composites shows a peculiar behavior as it becomes larger than one half or less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…This is due to the anisotropy mentioned earlier. It is interesting to note that the only auxetic behaviour designed into glass/epoxy laminates was in [13,19]. The work performed here has shown that the glass/epoxy laminates based on a [±θ 2 ] s configuration always have a positive ν 13 and ν 23 due to the lack of anisotropy in the prepreg material.…”
Section: Discussionmentioning
confidence: 88%
“…This is due to the anisotropy mentioned earlier. It is interesting to note that the only auxetic behaviour designed into glass/epoxy laminates was in [13,19]. The work performed here has shown that the glass/epoxy laminates based on a [±θ 2 ] s configuration always have a positive ν 13 and ν 23 due to the lack of anisotropy in the prepreg material.…”
Section: Discussionmentioning
confidence: 88%
“…Composite laminate structures can display negative Poisson's ratios (Tsai and Hahn 1980), the more anisotropic the plies, the more readily (Yeh et al 1999) negative Poisson's ratios are observed. The abdominal wall is composed of three sheet-like muscles and their corresponding aponeuroses overlying each other, each with what has been anecdotally described as loose connective tissue intervening (Bendavid and Howarth 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Ply orientations for generating maximum negative Poisson's ratio in a composite laminate are close to 70 /20 . [89] Yeh et al [90] demonstrated that by using specific values of elastic constants E 1 , E 2 , G 12 , and n 12 in each lamina; a composite laminate with negative in-plane Poisson's ratio can be generated. It is important that the ply material should be anisotropic for generating through thickness negative Poisson's ratios in composite laminates.…”
Section: Auxetic Compositesmentioning
confidence: 99%